Ofatumumab retreatment and maintenance in fludarabine‐refractory chronic lymphocytic leukaemia patients. (30th March 2015) - Österborg, Anders; Wierda, William G.; Mayer, Jiří; Hess, Georg; Hillmen, Peter; Schetelig, Johannes; Schuh, Anna; Smolej, Lukáš; Beck, Christian; Dreyfus, Brigitte; Hellman, Andrzej; Kozlowski, Piotr; et al.
Summary There are limited data on retreatment with monoclonal antibodies (mAb) in patients with chronic lymphocytic leukaemia (CLL). In a pivotal study, ofatumumab (human anti‐CD20 mAb) monotherapy demonstrated a 47% objective response rate (ORR) in fludarabine refractory CLL patients. From this study, a subset of 29 patients who had at least stable disease and then progressed were retreated with eight weekly ofatumumab infusions (induction treatment period), followed by monthly infusions for up to 2 years (maintenance treatment period). The ORR after 8 weeks of induction retreatment was 45% and 24% had continued disease control after maintenance at 52 weeks. Efficacy and safety of the retreated patients were compared with their initial results in the pivotal study. Response duration was 24·1 months vs. 6·8 months; time to next therapy was 14·8 months vs. 12·3 months; and progression‐free survival was 7·4 months vs. 7·9 months (medians). Upon retreatment, 72% had infusion reactions, mostly Grade 1–2. Three patients had fatal infections. In summary, ofatumumab retreatment and maintenance therapy was feasible in patients with heavily pretreated CLL and appeared to result in more durable disease control than initial ofatumumab treatment in this subset of patients who may have a more favourable disease profile.